Respuesta :

Let's see first x-y=-3. You can find x and x=-3+y
Then you replace x in x+3y=5
-3+y+3y=5
4y=8
y=2 But you have to find x too.
x=-3+2 x=-1
The answers are x=-1, y=2

Answer:

x = -1

Step-by-step explanation:

The system of equations is given as x - y = -3 --------(1) and

x + 3y = 5 -------(2)

We have to find the value of x

For which we will eliminate y from these equations.

We multiply equation (1) by 3 and add it to equation (2)

3(x-y) + (x+3y) = -9 + 5

(3x + x) + (3y - 3y) = -4

4x = -4

x = -1